Preliminary studies on the transformation of nitrosugars into branched chain iminosugars: synthesis of 1,4-dideoxy-4-C-hydroxymethyl-1,4-imino-pentanols. - Otero, J; Soengas, R; Estévez, J; Estévez, R; Watkin, D; Evinson, E; Nash, R; Fleet, G (2007)
A novel promising strategy for the transformation of nitrosugars into branched pyrrolidines, based on double Henry reaction with formaldehyde followed by reductive ring closure, allowed the first enantiospecific synthesis of a 4-C-hydroxymethyl branched derivative of the well-known glycosidase inhibitor 1,4-dideoxy-1,4-imino-pentanol. This strategy also afforded a new route to some other interesting derivatives, such as N-hydroxy, N-propyloxy, and imino derivatives, a new kind of compounds with promising biological properties. [reaction: see text].